Full-Sib family selection in maize populations for tolerance to low soil nitrogen - Ajala, S.; Kling, J.; Menkir, A. (Informa UK Limited, 2012)
Improving maize productivity in the savannas of West Africa will depend on improving soil fertility and ensuring the efficient use of inputs and the relevant maize varieties tolerant to low nitrogen (N) that have been developed for this region. Several cycles of full-sib family selection that combine agronomic performance under low N with yield under high N to maximize gains under both environments have been used to improve three such developed populations. Evaluation of different cycles of selection revealed that desirable changes in gene frequencies had taken place after three cycles of selection in two of the three populations, leading to a yield gain of over 200 kg/ha/cycle under 30 kg N/ha and over 270 kg/ha/cycle under 90 kg N/ha. Trends in performance of the third population under low N simply indicated that additional cycles of selection would be required to shift gene frequencies significantly in the direction of increased yield production. This yield gain did not adversely affect other agronomic traits. Therefore, improving maize for tolerance to low soil N in West and Central Africa is feasible without compromising grain yield performance under high-N application.